Co‐located and distributed natural‐language requirements specification: traditional versus reuse‐based techniques. Issue 3 (26th February 2016) - Carrillo de Gea, Juan M.; Nicolás, Joaquín; Fernández Alemán, José L.; Toval, Ambrosio; Ouhbi, Sofia; Idri, Ali
Abstract: Requirements Engineering (RE) includes processes intended to elicit, analyse, specify and validate systems and software requirements throughout the software life cycle. Mastering the principles of RE is key to achieving the goals of better, cheaper and quicker systems and software development projects. It is also important to be prepared to work with remote teammates, as distributed and global projects are becoming more common. This paper presents an experiment with a total of 31 students from two universities in Spain and Morocco who were assigned to either a co‐located or a distributed team. Both traditional and reuse‐based requirements specification techniques were applied by the participants to produce requirements documents. Their outcomes were then analysed, and the approaches were compared from the point of view of their effect on a set of performance‐based and perception‐based variables in co‐located and distributed settings. We found significant differences in only productivity ( Z  = −2.320, p  = 0.020) and difficulty ( Z  = −2.124, p  = 0.034) as regards the scores attained for non‐reuse and reuse conditions, both in the co‐located modality. Our findings show that, in general, the participants attained similar results for requirements specification when using the two strategies in both distributed and non‐distributed environments. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper compares the specification of requirements from source documents and from a catalogue of reusable requirements, in co‐located and distributed settings. No statistically significant differences were found from the point of view of most of the variables of our theoretical evaluation model. Our conclusion is that both appropriate tool support and sufficient specific training are required if the expected benefits of catalogue‐based requirements reuse are to be achieved.